AGRICULTURAL AND PLANTATION PRODUCT MARKETING INFORMATION SYSTEM - Ade Nisa Refitasari; Hilda Dwi Yunita; Yodhi Yuniarthe (PT. Alesha Media Digital, 2022)
The agricultural and plantation sectors play a key part in Indonesia's economic development. This is because the majority of Indonesians continue to rely on this industry for their lives, particularly as a provider of basics. Farmers in Marga Agung Village, Jati Agung District, South Lampung are one example. Currently, farmers purchase and sell agricultural products through agents, wholesalers, retailers, and consumers who rely on the conventional marketing system, resulting in a number of issues, such as the difficulty of selling suitable agricultural products. These agricultural products are getting more expensive in Indonesia, both in the eyes of customers and due to farmers' meager profit margins. Consequently, a WEB-based marketing system was developed utilizing a design methodology that employs the UML Tool. The objective and benefits of building this website are to promote agricultural and plantation products, to facilitate the purchase and sale of agricultural and plantation products by farmers, and to facilitate the acquisition of agricultural and plantation products by consumers.